What has been written about Jan Korensky (the person) and his texts - Hoffmannova, Jana (Bohemica Olomucensia, 2024)
This contribution is an attempt to create a portrait of Jan Korensky from the opinions and quotes of around twenty Czech and Slovak linguists, i. e. of Korensky's peers, colleagues and students. The selection is based on texts written about him and his work: reviews of his books, texts celebrating his life milestones, and (unfortunately) also obituaries.
Keywords: Jan Korensky; biographical portraits; reviews; obituaries; pragmatic turn; communicative grammar; functional stratification of Czech; play; chaos; rationality